Practicing Patriarchy in Islam: Are there Equality and Justice in The Role and Position in Islam? - Ega Nur Fadillah; Erni Heriyanti; Nur Saebah (Syntax Literate, 2022)
This research aims to analyze the role and position of women in Islam with the argument that there is a distinct practice of patriarchy in Islam. Therefore, this research searches for the principles of equality and justice that may be contained in the Al-Quran and Hadith, as well as some examples of the life of the Prophet Muhammad and the practice of the early period of Islam showing women's active participation in various aspects of life. This research shows the findings that support the perspective of Islamic teachings which are in line with the principles of gender equality. The method used in this study is through literature study accumulating from some previous research to explain how religious texts, such as the Qur'an and Hadith are interpreted to shape gender dynamics in Islamic societies, and the factors that influence patriarchal manifestations in Islamic societies. The article shows that this essay contends that it is important to socialize the universalist values found in Islamic holy scriptures that support justice, respect women's rights, and work toward achieving equality between different genders that can be implemented in Muslim societies. The dissemination of this gender-sensitive interpretation of Islamic literature should aim to raise public knowledge of issues relating to women's rights and gender equality in Islam.